2014
DOI: 10.1007/s12325-014-0151-7
|View full text |Cite
|
Sign up to set email alerts
|

Fixed-Dose Combination of Tafluprost and Timolol in the Treatment of Open-Angle Glaucoma and Ocular Hypertension: Comparison with Other Fixed-Combination Products

Abstract: A new preservative-free fixed-dose combination of 0.0015% tafluprost, a prostaglandin F2α analog, and 0.5% timolol (TAF/TIM; Santen Oy, Tampere, Finland), a beta-adrenergic antagonist has recently been developed. The intraocular pressure (IOP) reduction with TAF/TIM in open-angle glaucoma and ocular hypertension is similar to that of other prostaglandin–timolol fixed-combination products. Patients with high IOP responded well to TAF/TIM with reductions of up to 40% (>13 mmHg) and beyond. Compared to previous c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
29
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 39 publications
(42 reference statements)
6
29
0
3
Order By: Relevance
“…At the final visit, individual IOPs were lower compared with baseline in 89.5% eyes, unchanged in 5.1% eyes and higher in 5.4% eyes. Interestingly, the IOP response seems to be dependent on the baseline IOP levels, which confirms earlier results: eyes with higher baseline IOP levels showed a higher absolute response and percentage IOP decrease as compared to eyes with lower baseline IOP levels 20. This result was found for patients with prior medical treatment and also for the subgroup of treatment-naïve patients.…”
Section: Discussionsupporting
confidence: 88%
“…At the final visit, individual IOPs were lower compared with baseline in 89.5% eyes, unchanged in 5.1% eyes and higher in 5.4% eyes. Interestingly, the IOP response seems to be dependent on the baseline IOP levels, which confirms earlier results: eyes with higher baseline IOP levels showed a higher absolute response and percentage IOP decrease as compared to eyes with lower baseline IOP levels 20. This result was found for patients with prior medical treatment and also for the subgroup of treatment-naïve patients.…”
Section: Discussionsupporting
confidence: 88%
“…Although comparisons across studies should be made with caution, data from the two phase III studies compare favourably with those reported for preservative-containing or -free fixed-dose combination therapies with a prostaglandin analogue and timolol (bimatoprost/timolol, latanoprost/timolol and travoprost/timolol) [23]. Tafluprost/timolol was well tolerated in clinical studies in adults with open-angle glaucoma or ocular hypertension (Sect.…”
Section: Current Status Of Tafluprost/timolol In Openangle Glaucoma Omentioning
confidence: 72%
“…In a systematic review21 comparing the four fixed dose timolol/PGA combinations, the IOP reduction with preservative-free tafluprost/timolol combination (from the two RCTs described above27,28) was similar to that of other PGA/timolol fixed combination products in previous studies (and heavily dependent on the baseline IOP). Hyperaemia occurred in 1.8–8.5% with latanoprost/timolol, 6.4–8.0% with tafluprost/timolol, 10.8–15.0% with travoprost/timolol and 19–26% with bimatoprost/timolol (no p values reported) 21.…”
Section: Drug Therapymentioning
confidence: 68%
“…Hyperaemia occurred in 1.8–8.5% with latanoprost/timolol, 6.4–8.0% with tafluprost/timolol, 10.8–15.0% with travoprost/timolol and 19–26% with bimatoprost/timolol (no p values reported) 21. Eye irritation occurred in 2.3–9.0% with latanoprost/timolol, 7.0–12.7% with tafluprost/timolol, 11.5–23.6% with travoprost/timolol and 8.5–23.8% with bimatoprost/timolol (no p values reported).…”
Section: Drug Therapymentioning
confidence: 97%
See 1 more Smart Citation